Impact of glacial meltwater on hydrography, biochemistry, and marine productivity in Northwest Greenlandic fjords - Emma Wolff 1999- (2024)
Greenlandic fjords are dynamic coastal areas that serve as major feeding and breeding grounds for various kinds of fish, birds, and mammals. These fjords typically receive meltwater from land- and/or marine-terminating glaciers. Throughout the Arctic region, freshwater discharge from glaciers is increasing with the changing climate. This raises questions about the possible consequences for the downstream marine environment. Previous research mainly focused on the impact of meltwater on fjord-glacier circulation, however little is known about the consequences for marine productivity. This study investigates the impact of glacial meltwater on hydrography, biochemistry, and marine production in four Northwest Greenlandic fjords with different characteristics, such as bathymetry and the type of glacier (marine or land-terminating glaciers) from which the meltwater originated. To investigate the impact of glacial meltwater, temperature and salinity measurements, dissolved macronutrients, phytoplankton, zooplankton community structure and distribution, and bird and commercial fishery data were analyzed from the different fjords. The results show that large freshwater input during summer from meltwater rivers, calving icebergs, and subglacial discharge lowers salinity near meltwater discharge points or marine-terminating glaciers. Except for Silica, macronutrients are generally low near discharge points. Stratification and high turbidity levels close to discharge points restrict light availability and nutrient replenishment, which negatively impacts phytoplankton amounts and zooplankton biomass and abundance. In case of a marine-terminating glacier, subglacial discharge causes upwelling of deep nutrient-rich water, sustaining high phytoplankton amounts and zooplankton production close to the meltwater plume. Copepods dominated the zooplankton community in both abundance (69.8%) and biomass (74.2%). The zooplankton community changes along the fjord axis, with large Calanus species dominating the mouth of the fjord. ...